ANESTEZJOLOGIA I INTENSYWNA TERAPIAThe influence of high frequency jet ventilation during lung decortications surgery for selected perioperative parameters - Misiołek, Hanna; Olejnik, Krzysztof; Czyżewski, Damian; Grzanka, Maja; Szczerbak, Grażyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
High frequency jet ventilation may be an alternative method of ventilation for thoracic surgery, in which disruption or significant reduction of mobility of the operated lung is important. The aim of this study was to assess the impact of the chosen method of intraoperative ventilation during lung decortication surgery. The following parameters were documented: duration of surgery and operating conditions, postoperative bleeding, duration of air leak from the pleura, the time of maintaining the tubing in the pleura and the time of hospitalization.  The anesthetic procedure was not different between groups (high frequency jet ventilation [HFJV] group = 19; one lung ventilation [OLV] group = 21). In the OLV group operating time was significantly longer. Blood loss was significantly higher during operations with OLV. The operating conditions were significantly better during HFJV. The method of intraoperative ventilation did not significantly affect the time or leakage  of air from the pleura, pleural drainage or the time of its maintenance. There was no effect of type of ventilation on the du- ration of hospitalization. High frequency ventilation may be an alternative method for OLV during lung decortication surgery, because of better operating conditions, shorter operative time and significantly less intraoperative bleeding.